The Effect of Self-Potential, Study Habits, and Numerical Abilities on The Mathematics Learning Outcomes of Junior High School Students - Bernard Bernard; Ahmad Talib; Megawati Megawati (PT Mattawang Mediatama Solution, 2022)
This study is a quantitative study with an ex post facto approach aimed at knowing the effect of self-potential, study habits and numerical abilities on the mathematics learning outcomes of junior high school students. The sample in this study was 78 students of SMP class VIII who were selected using simple random sampling technique. The data collection technique used in this research is the test and questionnaire method. The instruments used are self-potential questionnaires, study habits questionnaires, numerical ability tests and mathematics learning outcomes tests. The data analysis technique used was multiple linear regression analysis. The results showed that: (1) Self-potential, study habits and numerical abilities together had an effect on students' mathematics learning outcomes, (2) Self-potential had a negative but not significant effect on students' mathematics learning outcomes, (3) study habits have a significant positive effect on students' mathematics learning outcomes, (4) numeric abilities have a significant positive effect on students' mathematics learning outcomes.